FIT negative cancers: A right-sided problem? Implications for screening and whether iron deficiency anaemia has a role to play. Issue 1 (February 2021) - Cunin, Laila; Khan, Aftab Alam; Ibrahim, Maria; Lango, Artemisia; Klimovskij, Michail; Harshen, Raj
Abstract: Introduction: Faecal Immunohistochemistry Testing (FIT) is recommended as an adjunct to guide referrals from Primary Care for individuals without rectal bleeding, who do not meet the suspected cancer pathway referral guidelines. It has largely replaced Faecal Occult Blood Testing. Aims: To assess the specificity of FIT. To understand the characteristics of FIT negative cancer patients and whether they have predominantly right sided cancers. Evaluating the efficacy of FIT and Iron deficiency anaemia in combination to capture patients with colorectal cancers. Methods: A study of 1000 symptomatic patients, undergoing FIT by Clinicians during the 'Digital rectal examination'. Inclusion criteria; all patients referred via our cancer referral pathway. FIT positivity was set at 10 μg g of faeces. Results: There were 7 FIT negative cancers in this cohort; 1 was a lymphoma and the other 6 were caecal adenocarcinomas. 5 were anaemic. The positive predictive value of IDA was 34% compared with 'other symptoms'; 18%. The negative predictive value of FIT was 99.05% in this cohort. Specificity for FIT was 86.9% (CI 96%). Conclusion: Two separate referral pathways for IDA and FIT positive tests, would have captured all patients except 2; the lymphoma and 1 advanced caecal adenocarcinoma. FIT is an excellent triage tool prior to colonoscopy however capturing right sided disease remains a weak point. Multivariate analysis of patients in addition to IDA and FIT should improve capture of this subgroup.